2024
DOI: 10.1073/pnas.2300582121
|View full text |Cite
|
Sign up to set email alerts
|

Rapid single-particle chemical imaging of nanoplastics by SRS microscopy

Naixin Qian,
Xin Gao,
Xiaoqi Lang
et al.

Abstract: Plastics are now omnipresent in our daily lives. The existence of microplastics (1 µm to 5 mm in length) and possibly even nanoplastics (<1 μm) has recently raised health concerns. In particular, nanoplastics are believed to be more toxic since their smaller size renders them much more amenable, compared to microplastics, to enter the human body. However, detecting nanoplastics imposes tremendous analytical challenges on both the nano-level sensitivity and the plastic-identifying specificity, leading to a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…1 illustrates the principle of bright-field imaging for determining the swelling kinetics of individual microplastic particles. To date, common microplastics such as polymethylmethacrylate (PMMA), polystyrene (PS), polyvinyl chloride (PVC), polypropylene (PP), polyethylene terephthalate (PET), and polyethylene (PE) 15,16 have come into use. These microplastic particles pose a tremendous risk to environmental safety and human health.…”
Section: Resultsmentioning
confidence: 99%
“…1 illustrates the principle of bright-field imaging for determining the swelling kinetics of individual microplastic particles. To date, common microplastics such as polymethylmethacrylate (PMMA), polystyrene (PS), polyvinyl chloride (PVC), polypropylene (PP), polyethylene terephthalate (PET), and polyethylene (PE) 15,16 have come into use. These microplastic particles pose a tremendous risk to environmental safety and human health.…”
Section: Resultsmentioning
confidence: 99%
“…Optical and electrochemical sensing strategies integrated with discrimination capability for the particle size and type represent a growing field. , In particular, different optical and/or electrochemical platforms were developed for this purpose. For instance, the coupling between optical tweezers and ML was demonstrated for microplastics classification in terms of both size and material . However, this approach was not proven for plastic nanoparticles and requires an expensive and complex experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, Doi et al demonstrated the use of optical tweezers to distinguish nano- and microparticles but without the discrimination of the material type. A very recent work proposes a sensing approach by hyperspectral stimulated Raman scattering (SRS) microscopy, demonstrating the nanoplastics classification in terms of different materials in water samples, but in this case too, the approach requires complex and expensive instrumentation. Analytical methods for microplastics characterization exploiting FTIR analysis coupled with AI-based tools were also available. , Additionally, the use of surface enhanced Raman scattering (SERS) substrates paves the way for micro- and nanoplastics identification .…”
Section: Discussionmentioning
confidence: 99%
“…5 The majority (54%) of PET is utilized for the production of textiles and fibers, another 24 MMT (or 29%) for rigid containers and single-use bottles, with the rest used in films and other applications. 6 Multiple chemical recycling strategies for PET have been developed over the last several decades and, in some cases, scaled up. 7−9 Their aim is also to potentially include PET substrates such as textiles that are not currently recycled.…”
Section: Introductionmentioning
confidence: 99%
“…Among plastics, poly­(ethylene terephthalate) (PET), a conjugate of terephthalic acid (TPA) and ethylene glycol (EG), is the most abundantly produced synthetic polyester in circulation today. , Production of PET has reached 82 million metric tons (MMT) per year . The majority (54%) of PET is utilized for the production of textiles and fibers, another 24 MMT (or 29%) for rigid containers and single-use bottles, with the rest used in films and other applications …”
Section: Introductionmentioning
confidence: 99%